2017
DOI: 10.4172/2329-6879.1000262
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Respiratory Health Symptoms and Associated Factor among Street Sweepers in Addis Ababa, Ethiopia

Abstract: Background: Occupational hazards are becoming the major concern for public health. Occupational health awareness in Ethiopia not well informed. And this resulted in extensively high prevalence of occupational respiratory symptoms. This research is aiming to assess occupational respiratory health symptoms and associated factors among street sweepers in Addis Ababa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Moreover, 15 studies revealed that street sweepers developed loss of lung elastic recoil pressure ( 28 ); impaired lung function ( 29 , 30 ); cough, phlegm, chest pain, sneezing, noisy breathing, nose irritation, rhinitis, cough, and wheezing ( 31 , 32 ). They developed an obstructive pattern of impaired lung functions and acute respiratory infection ( 33 39 ). The respiratory problems observed among street sweepers were due to the exposure of dust to lung functions ( 40 ) which leads to decreased lung function due to dust exposure ( 41 ); and lung impairment ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 15 studies revealed that street sweepers developed loss of lung elastic recoil pressure ( 28 ); impaired lung function ( 29 , 30 ); cough, phlegm, chest pain, sneezing, noisy breathing, nose irritation, rhinitis, cough, and wheezing ( 31 , 32 ). They developed an obstructive pattern of impaired lung functions and acute respiratory infection ( 33 39 ). The respiratory problems observed among street sweepers were due to the exposure of dust to lung functions ( 40 ) which leads to decreased lung function due to dust exposure ( 41 ); and lung impairment ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…New materials are introduced to the workplace every year ( 14 ) and ORD is also occasionally caused by working in hospitals and office buildings ( 15 ). It was indicated that bakers, kitchen workers, waste collectors, cleaners, healthcare staff, hairdressers, farmers and textile industry workers suffer from occupational allergic disorders ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Respiratory symptom among street sweepers were reported in different regions of the world including Tanzania, 3 Iran, 6 India, 7 Nigeria, 47.3% of participants, 8 and in different parts of Ethiopia, such as Dessie and Kombolcha, 45.4%, with the prevalence of cough, 16.54%, phlegm, 15.4%, wheezing, 32.3%, breathlessness, 21.3%, and chest pain, 14.3%, 9 and Addis Ababa, in 2017, 68.9%, 10 and 2018, 70.3%. 11…”
Section: Introductionmentioning
confidence: 99%
“…4 Occupational respiratory diseases are the most serious public health problem, accounting for 30% of all registered work-related diseases and 10% to 20% of all deaths worldwide, and as a result of poor working conditions it is a significant burden in low and middle-income countries. 5 Respiratory symptom among street sweepers were reported in different regions of the world including Tanzania, 3 Iran, 6 India, 7 Nigeria, 47.3% of participants, 8 and in different parts of Ethiopia, such as Dessie and Kombolcha, 45.4%, with the prevalence of cough, 16.54%, phlegm, 15.4%, wheezing, 32.3%, breathlessness, 21.3%, and chest pain, 14.3%, 9 and Addis Ababa, in 2017, 68.9%, 10 and 2018, 70.3%. 11 There are a number of factors that affect respiratory symptoms and reported in different studies and such factors including socio-demographic characteristics like age, 11 BMI, sleeping hours, 12 educational level, housing condition factors like direct contact with pets, artificial or natural ventilation, 13 use of coal/ wood for cooking, 14 behavioral related factors like smoking, 15 personal protective equipments (PPE) utilization, 14 Environmental Health Insights experience or duration of exposure, working hours per day, 11 and past respiratory illness.…”
Section: Introductionmentioning
confidence: 99%